The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11101-009-9122-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of organic sulfur compounds from Allium species in cancer prevention and therapy

Abstract: Phytochemical research has revealed that organic sulfur-containing compounds (OSCs) from Allium species exert biological effects, that might be beneficial in the treatment or prevention of a range of diseases, such as infections, cardiovascular and metabolic affections, cancers and related indispositions. Focusing physiological activities of these compounds in the context of cancer, it became clear from both epidemiological studies in men and experimental studies in diverse models, that the OSCs have a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 133 publications
0
15
0
Order By: Relevance
“…Recent studies have confirmed that various organic sulfur compounds exhibit anticancer properties (22) and their efficiency was demonstrated in vitro and in vivo on various cancer types (5-8,23). These compounds appear to target different signaling pathways to inhibit cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have confirmed that various organic sulfur compounds exhibit anticancer properties (22) and their efficiency was demonstrated in vitro and in vivo on various cancer types (5-8,23). These compounds appear to target different signaling pathways to inhibit cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Many of Allium organo-sulfurous compounds have been already identified to have anti-oxidant defense mechanisms, which are mainly mediated by thiols together with their corresponding disulfides, making up an intracellular redox-buffer 26 . Alliin isolated from A. sativum have been reported to have potent reducing abilities when examined by the 1,1-diphenyl-2-picrylhydrazyl DPPH stable free radical scavenging assay.…”
Section: Discussionmentioning
confidence: 99%
“…The high content of organo-sulphur compounds in this essential oil can explain the antioxidant activity of this essential oil but more studies were needed to elucidate mechanisms. A promising strategy for targeting redox status of the cells was to use readily available natural substances from Allium vegetables food 2,26 .…”
Section: Discussionmentioning
confidence: 99%
“…104 Garlic and related allyl sulfur compounds block tumors in the colon, lung, breast, liver and tumor proliferation/apoptosis. 105,106,107,108,109 Alterations in glutathione: oxidized glutathione ratios, shift in sulfhydryl groups and resultant changes in cellular redox status may be involved in some of the phenotypic changes caused by allyl sulfur compounds and it may also cause hyper phosphorylation of specific cell cycle proteins and histone hyperacetylation that has correlation with suppression tumor cell proliferation. 110,111 The anticancer effect of diallyltrisulfide in human colon cancer cells HCT-15 and DLD-1 was due to disrupted microtubule network formation of the cells 112 (Milner et al, 2009).…”
Section: Garlic (Allium Sativa)mentioning
confidence: 99%